Photogrammetric Quantification Analysis of Forward Head Posture Among Healthy Participants and Subjects with Neck & Shoulder Pain- A Strobe Cross Sectional Study - Sindhuja, Munuswamy; Kanimozhiselvi Sounderrajan, Jamunarani; Radhika, Jayaraman (INTI International University, 2023)
Background:Musculoskeletal structures can change into an incorrect shape due to a reduction in physical activity and inappropriate posture habits in daily living. Aim of the study: To study and investigate the forward head posture which is related to shoulder and neck pain. Materials and Method: The design of this study was observational cross-sectional study and conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology Statement (STROBE). The study was conducted between January 2023 and March 2023. A total of 65 participants (42 males,23 females) aged 18- 35 years. Neck pain was measured using Neck Disability Index (NDI), shoulder pain was measured using DASH questionnaire, Forward Head Posture (FHP) was measured using CVA angle by photogrammetry. Theresults were compared and correlated using appropriate statistical tools.For data analysis, the computer program Statistical Social Science Package (SPSS) (19 windows version) has been used. The p value was considered < 0.01 considered quite significant. Conclusion: Cervical and shoulder pain, which is the causative factor to increase forward head posture and significant discomfort in all the participants.